Limit equilibrium models for active failures of large-diameter shield tunnel faces in soft clay reinforced with soil–cement walls. (January 2023) - Su, Dong; Song, Qilong; Lin, Xingtao; Li, Qiang; Chen, Xiangsheng
Abstract: To prevent face collapses during shield tunneling, it is necessary to reinforce soft ground; however, thus far, the stability of tunnel faces in reinforced ground has not been investigated thoroughly. In this paper, finite-element analyses were first conducted to explore the failure mechanism of tunnel faces in reinforced soft soil, with a focus on the influence of the distance between the tunnel face and the cement wall, L. The limit support pressure acting on the tunnel face was determined, and the failure zone of the soil in front of the tunnel face was elucidated for cases involving different values of L . Thereafter, three types of failure modes—the full-penetration, partial-penetration, and non-penetration modes—were identified based on the development of the shear strain in the soil. The corresponding failure models were established based on the limit equilibrium method, and analytical expressions for calculating the limit support pressure were derived. The prediction results obtained using the proposed formulas were in good agreement with the results of numerical simulations; this indicates that the proposed collapse models can accurately reflect the impact of the face–wall distance, L, on the stability of shallow tunnel face in soft clay reinforced with soil–cement wall.